TAGGING GENES FOR VELVET HAIRINESS IN UPLAND COTTON - S. U. Rahman; T. A. Malik; S. T. Malik (Journal of Animal and Plant Sciences, 2013)
Small hairs on leaves and stems also known as trichomes are biologically an important insect resistant trait in cotton. Variations in form, function and distribution of hairs within a species have been exploited for developing insect resistant cotton cultivars. The DNA marker for the velvet hairiness trait was identified by RAPD technique using bulked segregant analysis. A cross of velvet hairy (densely hairy) and sparsely hairy genotypes was made and segregating F2 generation was developed for DNA marker studies. Out of the 320 RAPD primers used, 36 showed polymorphism between the parents. The primer, GLG-6975 showed tight linkage with velvet hairy trait in the F2 population. This RAPD marker may be used in molecular breeding of cotton for insect resistance.
Keywords: Velvet Hairiness; Primer; RAPD; Upland Cotton